Rheohaemapheresis in the treatment of nonvascular age-related macular degeneration - Blaha, M; Rencova, E; Langrova, H; Studnicka, J; Blaha, V; Rozsival, P; Lanska, M; Sobotka, L (Atherosclerosis. Supplements, 2013)
PURPOSE: To evaluate the experience with rheohaemapheresis (RH) in the treatment of age-related macular degeneration (AMD). METHODS: Thirty-eight patients were each treated with 8 procedures of RH (14 males, 24 females). The control group consisted of 34 random patients (30 females, 4 males) with the dry form of AMD but not treated by RH. Our modification of the cascade method (named rheohaemapheresis) was used for plasma separation. After plasma separation (blood cell separator, Cobe Spectra, Denver, CO, USA), the separated plasma was pumped through a rheofilter (Evaflux 4A, Kuraray, Osaka, Japan) to remove lipoproteins and other high-molecular-weight rheologic factors. RESULTS: In treated patients, best-corrected visual acuity (BCVA) increased significantly from 0.61 (0.06-1.00) to 0.68 (0.35-1.00) after 2.5 years (p = 0.035). We found no significant changes or differences in scotopic activity, whereas cone response and paramacular activity in the more peripheral region between 14° and 22° of eccentricity were significantly higher in treated patients after 2.5 years. CONCLUSION: RH therapy favourably influenced BCVA. During 2.5 years after the therapy, no progression of dry to wet AMD was observed in our patients. RH reduced the area of drusenoid retinal pigment epithelium detachment (which increased during the natural course of dry form AMD). RH influenced rheological markers and probably improved metabolism in the affected retinal areas which lead to the aforementioned positive results.
Keywords: výsledek terapie; optická koherentní tomografie; viskozita krve; Recovery of Function; Lipoproteins; Male; zraková ostrost; biologické markery; Night Vision; Rheology; obnova funkce; progrese nemoci; Electroretinography; Biomarkers; Macular Degeneration; lipoproteiny; separace krevních složek; Česká republika; Blood Viscosity; reologie; Aged; mužské pohlaví; senioři; Disease Progression; Visual Acuity; Czech Republic; Time Factors; Treatment Outcome; senioři nad 80 let; lidé; ženské pohlaví; Humans; makulární degenerace; časové faktory; Tomography, Optical Coherence; Aged, 80 and over; prediktivní hodnota testů; noční vidění; elektroretinografie; Female; Predictive Value of Tests; Blood Component Removal